Phytochemical analysis and GC-MS profiling in the flower of Plumeria alba - Siti Aisyah, Mohamad; Noor Suhana, Adzahar; Akhtar, Muhammad Nadeem; Zareen, Seema; Lee, Thong Chuan (Trans Tech Publications, Switzerland, 2019)
Therapeutic properties of the medicinal plant are due to the presence of phytochemical constituents. The phytochemical constituents of Plumeria alba flower were investigated by phytochemical screening assays and gas chromatography-mass spectrometry (GC-MS). The phytochemical screening of hexane, dichloromethane, ethyl acetate, butanol, and aqueous extracts of P. alba flower showed it contains a various concentration of saponins, flavonoids, tannins, steroids, volatile oil and phenolic compounds. Several major chemical constituents that were identified is squalene, bis(2-ethylhexyl) phthalate, methyl (methyl 4-O-methyl-α-d-mannopyranoside) uronate and tricyclo [7.2.0.0(2,6)] undecan-5-ol, 2,6,10,10-tetramethyl- (isomer 2) by using GC-MS technique.